Comment on Gattoni et al: sleep deprivation training as a highway to hell in ultratrail - Millet, G. P.; Hermand, E.; Hurdiel, R. (International Journal of Sports Physiology and Performance, 2022)
Comment on Gattoni et al: Sleep deprivation training to reduce the negative effects of sleep loss on endurance performance: a single case study (SPONET-ID 4074380)